Armenia between Byzantium and the Orient
1 online resource.
Keywords: This volume commemorating the late Armenian scholar Karen Yuzbashyan comprises studies of mediaeval Armenian culture, including the reception of biblical and parabiblical texts, theological literature, liturgy, hagiography, manuscript studies, Church history and secular history, and Christian art and material culture. Special attention is paid to early Christian and late Jewish texts and traditions preserved in documents written in Armenian. Several contributions focus on the interactions of Armenia with other cultures both within and outside the Byzantine Commonwealth: Greek, Georgian, Syriac, Coptic, Ethiopic, and Iranian. Select contributions may serve as initial reference works for their respective topics (the catalogue of Armenian khachkars in the diaspora and the list of Armenian Catholicoi in Tzovk’).